Lightning activity in the Southern Coast of Chile - Nicora, M. Gabriela; Garreaud, René D.; Bürgesser, Rodrigo E.; Ávila, Eldo E.; Quel, Eduardo J. (2021)
Ponencia presentada en la XV International Conference on Atmospheric Electricity, 15-20 June 2014, Norman, Oklahoma, U.S.A.